Chemical weapons: an overview of types, risks, and treatments - Muñoz-Canales, Verónica (2021)
Chemical weapons have been used since time immemorial with a particular boom during the 19th century and World War I, where they played a crucial role as weapons of mass destruction. Despite the current greater awareness on the part of the population, the danger of chemical agents has not ended, due to the increase in their use for terrorist purposes. In this paper, a classification of the different chemical weapons is carried out and their toxic effects and mechanisms of action are analyzed, among other aspects, to continue raising awareness about the importance of their prohibition.